2020
DOI: 10.3762/bjnano.11.45
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the relationship between viscoelastic properties and the invasion of ovarian cancer cells by atomic force microscopy

Abstract: The mechanical properties of cells could serve as an indicator for disease progression and early cancer diagnosis. This study utilized atomic force microscopy (AFM) to measure the viscoelastic properties of ovarian cancer cells and then examined the association with the invasion of ovarian cancer at the level of living single cells. Elasticity and viscosity of the ovarian cancer cells OVCAR-3 and HO-8910 are significantly lower than those of the human ovarian surface epithelial cell (HOSEpiC) control. Further … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Utilizing various techniques such as the optical stretcher, atomic force microscopy (AFM), shear assays, and magnetic tweezers, the invasiveness of metastatic cancer cells has been demonstrated to correlate with their viscoelastic properties [6][7][8][9][10][11]. For example, using a shear assay technique, Hu et al found that the stiffness of MCF-10A normal breast cells was about 10 times higher than that the stiffness of the highly metastatic MDA-MB-231 breast cancer cells, and attributed these differences to differences in the levels of actin expression and organization [11].…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing various techniques such as the optical stretcher, atomic force microscopy (AFM), shear assays, and magnetic tweezers, the invasiveness of metastatic cancer cells has been demonstrated to correlate with their viscoelastic properties [6][7][8][9][10][11]. For example, using a shear assay technique, Hu et al found that the stiffness of MCF-10A normal breast cells was about 10 times higher than that the stiffness of the highly metastatic MDA-MB-231 breast cancer cells, and attributed these differences to differences in the levels of actin expression and organization [11].…”
Section: Introductionmentioning
confidence: 99%
“…In short, The higher incidence of carcinoma out of teratoma and serous tumors may be related to the intense alteration of mechanical features of the cellular and ECM, serving as a potential risk factor which necessitates further investigation (64). A similar outcome was found in a study by Chen et al (65) the elasticity and viscosity of ovarian cancer cells OVCAR-3 (1195.72 ± 122.94Pa) and HO-8910 (996.27 ± 52.56Pa) were significantly lower than those of human ovarian surface epithelial cells (2160.94 ± 167.77 Pa) (65). Further detection showed that the migration/invasion ability of OVCAR-3 and HO-8910 cells was significantly higher than that of the control group.…”
Section: Elastic Changes Of Ovarian Cancer Cellsmentioning
confidence: 54%
“…We selected the properties of these groups by considering 24 different types of cells including healthy epithelial cells and carcinoma cells from several tissues (breast, lung, prostate, ovaries, bladder) as well as healthy and malignant leukocytes (leukemia, lymphoma). [ 4,57–69 ] A total of 50 randomized simulations were conducted for each of the pillar configurations.…”
Section: Methodsmentioning
confidence: 99%